Criteria for the selective use of chest computed tomography in blunt trauma patients - Brink, Monique (Springer-Verlag, 2009)
PURPOSE: The purpose of this study was to derive parameters that predict which high-energy blunt trauma patients should undergo computed tomography (CT) for detection of chest injury. METHODS: This observational study prospectively included consecutive patients (≥16 years old) who underwent multidetector CT of the chest after a high-energy mechanism of blunt trauma in one trauma centre. RESULTS: We included 1,047 patients (median age, 37; 70% male), of whom 508 had chest injuries identified by CT. Using logistic regression, we identified nine predictors of chest injury presence on CT (age ≥55 years, abnormal chest physical examination, altered sensorium, abnormal thoracic spine physical examination, abnormal chest conventional radiography (CR), abnormal thoracic spine CR, abnormal pelvic CR or abdominal ultrasound, base excess <−3 mmol/l and haemoglobin <6 mmol/l). Of 855 patients with ≥1 positive predictors, 484 had injury on CT (95% of all 508 patients with injury). Of all 192 patients with no positive predictor, 24 (13%) had chest injury, of whom 4 (2%) had injuries that were considered clinically relevant. CONCLUSION: Omission of CT in patients without any positive predictor could reduce imaging frequency by 18%, while most clinically relevant chest injuries remain adequately detected.